Analisis Penerapan Karakter Kepemimpinan Siswa Kelas V SDN Ngaliyan 03 Dalam Kegiatan Ekstrakurikuler Pramuka - Janah, Dyah Nur Hidayatun; Maharani, Putri; Fitammami, Vrida; Tsania, Jihan Zahra; Kiptiyah, Siti Maryatul (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Scouting education can be used as a strategic step in efforts to implement the leadership character that exists within students. Scout activities at SD 03 Ngaliyan are carried out outdoors so as to provide an element of creativity and exploration for students. Through scout activities, students are trained and guided in developing skills and character values, good leadership attitudes. The aim of this research is to analyze the application of leadership characteri of fifth grade students at SDN Ngaliyan 03 through scout extracurricular activities. The research method used in this research is descriptive qualitative, namely looking at phenomena that occur in the field to obtain data and describe it systematically so that it is easy to understand. And the techniques used are observation, interviews and documentation. The results of this research show that the application of leadership character through Scout extracurricular activities can be declared effective in its implementation, with 90% of the results in the "Good" category.